Fuzzy Labeling on Cycle Related Graph - MK, Pandurangan; T, Bharathi; Vinoth, S. Antony (International Journal of Computer Sciences and Engineering, 2019)
In this paper the concept of fuzzy labeling of fan graph has been introduced, the generalized formula for n- dimensional fan of the vertices and edges and the new algorithm of fuzzy labelling of fan graph have been discussed. Every membership function of fuzzy labeling of a fan graph must be distinct.